La mística como dispositivo profanador. Una clave para trabajar el diálogo interreligioso contemporáneo (2021)
The present work offers a proposal for an approach to mysticism from the category of profaning device present in the thought of Giorgio Agamben. Agambian desecration is rooted in the consideration that capitalism, as a socio-economic and political model, is understood from a religious and sacred structure, fundamentally visible and univocal, and, therefore, marked by the fundamentalism of its practices. Given this, mysticism would come to constitute a device that desecrates the religious mechanism of the market from apophatic language, the experience of recognizing the Mystery or of thinking about new possibilities of understanding and living the religious experience. These elements suppose, in turn, the recognition of an openness to new religious-social modulations that come to unblock and look critically at the religious and political fundamentalism of market religion. In this way, we seek to offer a reflection that allows interreligious dialogue to be worked as a suggestive way of thinking from other voices, in a clear plural opening and contrary to the closed vision typical of capitalist religiosity.